An aqueous copper battery enabled by Cu2+/Cu+ and Cu3+/Cu2+ redox conversion chemistry. Issue 72 (23rd August 2022) - Duan, Zeang; Zhao, Jiajin; Qi, Yadi; Li, Ruyue; Wang, Wenfeng; Peng, Qiuming; Han, Shumin; Zhang, Lu
Abstract : An aqueous copper battery comprising of an activated carbon cathode and Cu anode operating on Cu 2+ /Cu and Cu 3+ /Cu 2+ vs. Cu + /Cu via a cuprous (Cu + ) chloridum complex charge carrier in a 30 m choline chloride + 1 m CuCl2 electrolyte is presented. Abstract : We propose an aqueous copper battery via Cu 2+ /Cu + and Cu 3+ /Cu 2+ redox conversion chemistry on an activated carbon (AC) electrode enabled by a 30 m ChCl + 1 m CuCl2 electrolyte, where Cu 3+ /Cu 2+ redox promotes the discharge capacity by ∼50 mA h g −1 at ∼1.0 V vs. Ag/AgCl with stable cycling.